Tecnología del lenguaje: una propuesta metodológica. parte A - Jesús Becerra (Estudios sobre las Culturas Contemporáneas)
A methodological proposal offering a perspective of symbolic proces-ses as an act of diegesis rather than signification which is performednot by means of signs, but of "functives". Fromthis, the authpr propo-ses the foundation of a diegetics or "diegethics" as a basis of commu-nicology.